Sistem penjemputan sampah untuk pengelolaan sampah terpadu di Komunitas Muda Berseri - Astadi Pangarso; Candra Wijayangka; Yulia Nur Hasanah; Patrick Adolf Telnoni; Rixard George Dillak; Roni Riandi; Azhar Humaira Syabani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The garbage pick-up system is a system that is used to collect waste from homes, offices or other places that are commonly carried out by the local government or private companies that have obtained permission to manage waste in an area. Rancatungku Village has a Young Berseri Community that manages the garbage pickup system, but the community still feels that the system is not effective and efficient. Pick-up schedules that are not on schedule and irregular as well as pick-ups that have to be done several times are problems that are often experienced by the community, so it is necessary to improve the appropriate garbage pickup system. The purpose of this community service activity is to create an on-demand garbage pickup system to reduce waste accumulation. The method used in this community service activity is to analyze the wants and needs of the community, build a garbage pickup system using a platform, conduct outreach and provide assistance using the garbage pickup platform. This community service activity involves academics, the Berseri Young Community, and the people of Rancatungku Village. The success of this activity resulted in the creation of a garbage pickup system on the website https://mudaberseri.com/ and the results of participant assessments via an online form which showed that the Muda Berseri Community and the community had had enough of the new garbage pickup system.